2021
DOI: 10.1002/prot.26053
|View full text |Cite
|
Sign up to set email alerts
|

A detailed mapping of the readily accessible disulphide bonds in the cortex of wool fibres

Abstract: Trichocyte keratin intermediate filament proteins (keratins) and keratin associated proteins (KAPs) differ from their epithelial equivalents by having significantly more cysteine residues. Interactions between these cysteine residues within a mammalian fiber, and the putative regular organization of interactions are likely important for defining fiber mechanical properties, and thus biological functionality of hairs. Here we extend a previous study of cysteine accessibility under different levels of exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…In the wool follicles of sheep, the KAPs are produced soon after the synthesis of keratins during the development of fibres in the follicle, and they are thought to cross-link with the KIFs by forming disulphide bonds with cysteine residues in the head and tail domains of the keratins [ 1 ]. The nature of this cross-linking is not well understood, and while co-immunoprecipitation studies have demonstrated an interaction between the head domain of human keratin K86 and KAP2-1 [ 2 ], and Western blot studies have demonstrated an interaction between the head domain of K85 and KAP8-1 [ 2 ], a complete understanding of which K and KAP cysteine thiol groups form disulphide bridges (be they inter- or intra-chain) is not well known, although the bulk of the most readily accessible cysteines in the KAPs are reported to be found close to either the N- or C-terminal domains in these proteins [ 3 ]. The KAPs are thought to play a critical role in regulating the physico-mechanical properties of the fibre.…”
Section: Introductionmentioning
confidence: 99%
“…In the wool follicles of sheep, the KAPs are produced soon after the synthesis of keratins during the development of fibres in the follicle, and they are thought to cross-link with the KIFs by forming disulphide bonds with cysteine residues in the head and tail domains of the keratins [ 1 ]. The nature of this cross-linking is not well understood, and while co-immunoprecipitation studies have demonstrated an interaction between the head domain of human keratin K86 and KAP2-1 [ 2 ], and Western blot studies have demonstrated an interaction between the head domain of K85 and KAP8-1 [ 2 ], a complete understanding of which K and KAP cysteine thiol groups form disulphide bridges (be they inter- or intra-chain) is not well known, although the bulk of the most readily accessible cysteines in the KAPs are reported to be found close to either the N- or C-terminal domains in these proteins [ 3 ]. The KAPs are thought to play a critical role in regulating the physico-mechanical properties of the fibre.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated in their work on disulphide crosslinking in human keratins that a number of intermolecular crosslinks exist in the coil two regions between pairs of heterodimers. Further insights in the accessibility of cysteines in trichocyte keratins has been achieved by Plowman et al [14].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we are well aware that our decision to neglect certain factors may impose limitations on to the current analysis. First, the assumption of a homogeneous reductive/oxidative treatment is of only limited validity (70,71), namely, in view of the differences of the accessibility of the disulfide bonds (72). Second, the treatment will impart changes/damage to the IFs as well as the matrix in hair (73,74).…”
Section: Discussionmentioning
confidence: 99%